2020
DOI: 10.1021/acs.jproteome.0c00248
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Extracellular Matrix Proteome across the Myotendinous Junction

Abstract: Pearson correlation plot based on raw intensity of ECM proteins found in GuHCl homogenate; heat map by ECM category of matrisome proteins identified in GuHCl homogenate from M, J, and T tissues; identification of ECM enriched in J; immunolocalization of COL22A1 and a muscle-specific marker; cell compartment statistics; matrisome category statistics; and experimental details on reagents used for IHC (PDF) Protein ID for GuHCl Samples (XLSX) Compartmentalization Buffer Table (XLSX) Protein IDs for Fractionated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 101 publications
2
61
2
Order By: Relevance
“…(Fig.S3B) In other words, these genes may work as candidates for important drivers of the main process in firboNPCs. These genes have been associated with matrix remodeling (Col14A1, col12a1, CHAD, CRTAC1, TNC, Lamb1) 39 , antioxidation (FTH1) 40 and inflammation (S100a8) 41 .…”
Section: Resultsmentioning
confidence: 99%
“…(Fig.S3B) In other words, these genes may work as candidates for important drivers of the main process in firboNPCs. These genes have been associated with matrix remodeling (Col14A1, col12a1, CHAD, CRTAC1, TNC, Lamb1) 39 , antioxidation (FTH1) 40 and inflammation (S100a8) 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Understanding that sarcoplasmatic invaginations and SCL are composed of collagen fibers, we suggest SCL changes as precursors in the ultrastructural remodeling of MTJ. Jacobson et al (2020) described several collagen types in MTJ, more specifically, collagen XXII, which plays an essential role in the structural integrity and stabilization of the region.…”
Section: Discussionmentioning
confidence: 99%
“…Protein analysis of the ECM of muscle-tendon units revealed that there are several proteins, specifically type V α3 collagen, and type XXII collagen, that occur primarily at the junction. 10,11 Research into this specific protein synthesis could inform strategies for development of native-like muscle-tendon interfaces, increasing the function and efficacy of engineered muscle-tendon units. Future studies should include analysis of additional MTJ specific proteins like type XXII collagen, over longer time periods, along with cell signaling pathways leading to increased focal adhesion expression.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In studies of proteomic analysis of muscle-tendon units, type XXII collagen was isolated in the myotendinous region and is thought to interact with α7ÎČ1 integrins. 10,11 While there is some understanding of the cellular response to various disorders in muscle and tendon tissue individually, there is less understanding of how disorders in a single tissue may further inhibit reparative processes and decrease function of the muscle-tendon unit.…”
Section: Introductionmentioning
confidence: 99%